Proteomic and metabolomic profiling of extracellular vesicles produced by human gut archaea - Viktoria Weinberger; Barbara Darnhofer; Himadri B. Thapa; Polona Mertelj; Régis Stentz; Emily Jones; Gerlinde Grabmann; Rokhsareh Mohammadzadeh; Tejus Shinde; Christina Karner; Jennifer Ober; Rokas Juodeikis; et al. (Nature Communications)
Abstract Gastrointestinal bacteria interact with the host and each other through various mechanisms, including the production of extracellular vesicles (EVs). However, the composition and potential roles of EVs released by gut archaea are poorly understood. Here, we study EVs produced by four strains of human gut-derived methanogenic archaea: Methanobrevibacter smithii ALI, M. smithii GRAZ-2, M. intestini, and Methanosphaera stadtmanae. The size (~130 nm) and morphology of these EVs are comparable to those of bacterial EVs. Proteomic and metabolomic analyses reveal that the archaeal EVs are enriched in putative adhesins or adhesin-like proteins, free glutamic and aspartic acid, and choline glycerophosphate. The archaeal EVs are taken up by macrophages in vitro and elicit species-specific responses in immune and epithelial cell lines, including production of chemokines such as CXCL9, CXCL11, and CX3CL1. The EVs produced by M. intestini strongly induce pro-inflammatory cytokine IL-8 in epithelial cells. Future work should examine whether archaeal EVs play roles in the interactions of archaea with other gut microbes and with the host.